The association between the Moyamoya disease susceptible gene RNF213 variant and incident cardiovascular disease in a general population: the Nagahama study. Issue 12 (12th December 2021) - Tabara, Yasuharu; Yamada, Hitomi; Setoh, Kazuya; Matsukawa, Manami; Takahashi, Meiko; Kawaguchi, Takahisa; Nakayama, Takeo; Matsuda, Fumihiko; Kosugi, Shinji
Abstract : Objective: An association between the Moyamoya disease susceptible gene ring finger protein 213 ( RNF213 ) variant and ischemic stroke and coronary artery disease has been suggested in case-control studies. We aimed to investigate the possible association between the RNF213 variant and the incidence of cardiovascular disease in a general population. Methods: The study participants consisted of 9153 Japanese community residents without history of cardiovascular disease. The clinical parameters employed in this analysis were observed at baseline between 2008 and 2010. The RNF213 p.R4859K variant was determined by TaqMan probe assay and then confirmed by Sanger sequencing. Results: During 8.52 years follow-up period, we observed 214 incident cases of cardiovascular diseases (99 total stroke cases, 119 major adverse cardiac event cases, including 4 cases of both). The incidence rate was higher for the variant allele carriers (120 cases; incidence rate, 71.0 per 10 000 person-years) than for the homozygotes of the wild-type allele (26.9), and the group differences achieved statistical significance ( P  = 0.009). Although the RNF213 variant was also associated with systolic blood pressure (dominant model: coefficient of 8.19 mmHg; P  < 0.001), the Cox regression analysis adjusted for major covariates including systolic blood pressure identified the RNF213 variant as an independent determinant for cardiovascular disease (hazard ratio of 3.41, P  = 0.002) and major adverse cardiac event (hazard ratio of 3.80, P  = 0.010) but not with total stroke ( P  = 0.102). Conclusion: The Moyamoya disease susceptible RNF213 variant was associated with blood pressure and the incidence of cardiovascular disease in a Japanese general population.